Sintering curing conductive paste for TOPCon and BC and preparation method of sintering curing conductive paste

By using TOPCon and BC sintered and curing conductive paste in photovoltaic cell production, and replacing some silver powder by silver-clad copper powder, the problems of high prices and high equipment costs in the existing technology are solved, and cost reduction and conductive performance improvement are achieved.

CN119694668APending Publication Date: 2025-03-25SUZHOU SILVI NANO TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411908603.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the production of existing photovoltaic cells, silver has high prices and equipment costs and yield problems, so low-cost solutions that replace silver are urgently needed.

Method used

A conductive paste that can replace part of the silver powder is prepared by mixing silver-covered copper powder with silver powder, glass powder, resin and solvent, and adding thixotropic agent and defiling additive.

Benefits of technology

By replacing some silver powder with silver coated copper powder, the production cost is significantly reduced, and the process is simple and reliable, improving the conductivity and photoelectric conversion efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119694668A_ABST
    Figure CN119694668A_ABST
Patent Text Reader

Abstract

The invention provides sintering curing conductive paste for TOPCon and BC and a preparation method of the sintering curing conductive paste. The preparation method of the sintering curing conductive paste for TOPCon and BC comprises the following steps: S1, uniformly mixing silver powder, silver-coated copper powder, glass powder, resin and a solvent to obtain primary slurry; s2, a thixotropic agent and a demolding auxiliary agent are added into the primary slurry and evenly mixed, the sintering and curing conductive slurry for TOPCon and BC is obtained, and the mass of the thixotropic agent accounts for 0.05%-1% of the mass of the sintering and curing conductive slurry for TOPCon and the mass of the demolding auxiliary agent account for 0.1%-5% of the mass of the sintering and curing conductive slurry for TOPCon and the mass of the sintering and curing conductive slurry for BC respectively. According to the preparation method of the sintering and curing conductive paste for TOPCon and BC, the cost can be reduced, and the process is simple and reliable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conductive paste, in particular to a sintering and curing conductive paste for TOPCon and BC and a preparation method thereof. Background Art

[0002] In the current photovoltaic cell production, there is overcapacity and the silver price is relatively high, so there is an urgent need to replace silver to reduce costs. However, the existing solutions mainly include pure copper electroplating solutions and pure copper slurry solutions. Among them, the pure copper electroplating solution requires material addition, subtraction and etching, which has high equipment cost and low yield. The pure copper slurry solution requires a large amount of protective gas, and the process is still uncontrollable, and the yield and process control problems are huge. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a sintering and curing conductive paste for TOPCon and BC and a preparation method thereof, which can reduce costs and has a simple and reliable process.

[0004] According to the first aspect of the present invention, a method for preparing a sintering and curing conductive paste for TOPCon and BC comprises the following steps:

[0005] S1, uniformly mixing silver powder, silver-coated copper powder, glass powder, resin and solvent to obtain a preliminary slurry;

[0006] S2, adding a thixotropic agent and a demolding aid to the preliminary slurry, and mixing them evenly to obtain the sintering and curing conductive slurry for TOPCon and BC,

[0007] The mass of the thixotropic agent and the demoulding aid accounts for 0.05% to 1% and 0.1% to 5% of the mass of the sintering and curing conductive paste for TOPCon and BC, respectively.

[0008] In some embodiments, in step S1, the silver powder includes a particle size of D 50 Silver powder with a particle size of 1.5 μm and a particle size of D 50 50nm silver powder;

[0009] The particle size D of the silver-coated copper powder 50 3~5μm.

[0010] In some embodiments, the step S1 further includes adding a dispersant.

[0011] Wherein, the particle size is D 50 The silver powder is 1.5 μm, and the particle size is D 50The mass ratio of the 50nm silver powder, the silver-coated copper powder, the glass powder, the resin, the solvent and the dispersant is (5-30): (5-30): (60-80): (1-4): (0.5-3): (2-8): (0.1-0.5).

[0012] Preferably, in step S1, the resin includes one or more of polyvinyl butyral, ABS resin, mixed epoxy resin, solid bisphenol A epoxy resin, pure monomer resin, phenolic resin, polymethyl methacrylate resin, polyvinyl acetate resin, thermoplastic acrylic resin or alkyd resin;

[0013] Preferably, in step S1, the solvent includes one or more of acetone, butanone, methyl isobutyl ketone, isophorone, ethylene glycol, propylene glycol, ethyl acetate, butyl acetate, xylene, terpineol, ethylene glycol ethyl ether, diethylene glycol butyl ether, dodecanol ester, dibutyl phthalate, dioctyl phthalate, dioctyl adipate, isopropanol, n-butanol, and cyclopentanone;

[0014] The dispersant includes one or more of polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene glycol, hexadecyltrimethylammonium chloride, octadecylamine acetate, oleic acid, stearic acid or palmitic acid.

[0015] In some implementation modes, step S2 specifically includes:

[0016] Adding a thixotropic agent and a demoulding aid to the preliminary slurry, uniformly mixing to obtain a mixed slurry, grinding the mixed slurry to obtain the sintering and curing conductive slurry for TOPCon and BC,

[0017] The mass of the thixotropic agent and the demoulding aid accounts for 0.05% to 1% and 0.1% to 5% of the mass of the sintering and curing conductive paste for TOPCon and BC, respectively.

[0018] Preferably, in step S2, the thixotropic agent includes one or more of hydrogenated castor oil, polyvinyl alcohol, and hydroxyethyl cellulose.

[0019] Preferably, in step S2, the demolding aid includes one or more of acrylic resin, polyurethane resin, polyester resin, and silicone resin.

[0020] In some embodiments, in step S2, grinding the mixed slurry specifically includes:

[0021] The mixed slurry is ground to a fineness of 0 to 10 μm.

[0022] The sintering-curing conductive paste for TOPCon and BC according to the embodiment of the second aspect of the present invention is prepared by the preparation method of the sintering-curing conductive paste for TOPCon and BC described in any embodiment of the first aspect.

[0023] Compared with the prior art, the present invention has at least the following beneficial effects:

[0024] The method for preparing the sintered-cured conductive paste for TOPCon and BC of the embodiment of the present invention allows the silver-coated copper powder to replace part of the silver powder by adding a suitable amount of thixotropic agent and a demolding aid, thereby preparing the sintered-cured conductive paste for TOPCon and BC, which greatly saves the process cost and the process flow is also relatively simple and effective.

[0025] Based on the following detailed description of specific embodiments of the present invention in conjunction with the accompanying drawings, those skilled in the art will become more aware of the above and other objects, advantages and features of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Hereinafter, some specific embodiments of the present invention will be described in detail in an exemplary and non-limiting manner with reference to the accompanying drawings. The same reference numerals in the accompanying drawings indicate the same or similar components or parts. It should be understood by those skilled in the art that these drawings are not necessarily drawn to scale. In the accompanying drawings:

[0027] Figure 1 It is a flow chart of a method for preparing a sintering-cured conductive paste for TOPCon and BC according to an embodiment of the present invention. DETAILED DESCRIPTION

[0028] In the description of this embodiment, it should be understood that the terms "length", "width", "height", "up", "down", "left", "right", "vertical", "horizontal", "bottom", "inside" and "outside" etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0029] As a specific embodiment of the present invention, the method for preparing the sintering and curing conductive paste for TOPCon and BC according to the first aspect of the present invention comprises the following steps:

[0030] S1, uniformly mixing silver powder, silver-coated copper powder, glass powder, resin and solvent to obtain a preliminary slurry;

[0031] S2. Add thixotropic agent and demolding aid to the preliminary slurry and mix them evenly to obtain sintering and curing conductive slurry for TOPCon and BC.

[0032] The mass of the thixotropic agent and the demoulding aid accounts for 0.05% to 1% and 0.1% to 5% of the mass of the sintering and curing conductive paste for TOPCon and BC respectively.

[0033] Specifically, the method for preparing the sintered-cured conductive paste for TOPCon and BC in the embodiment of the present invention firstly uniformly mixes silver powder, silver-coated copper powder, glass powder, resin and solvent to obtain a preliminary slurry, and then adds a thixotropic agent and a demolding aid to the slurry to finally obtain the sintered-cured conductive paste for TOPCon and BC. The process is simple and reliable, and the silver-coated copper powder is used to replace part of the silver powder, which greatly reduces the production cost.

[0034] Among them, the thixotropic agent is mainly used to adapt to the slurry's own resin system, which can adjust the slurry's viscosity and thixotropy and improve the leveling performance of the rubber compound. The demolding agent mainly plays a role in selecting the system compatible with the needs, and can achieve a good demolding effect, making the surface smoother, and does not affect the conductivity and rheological properties of the slurry. In short, the amount of thixotropic agent and demolding agent can be determined according to the performance of the slurry itself. Adding too little will not achieve the leveling effect and the demolding effect is not obvious. Adding too much will affect the overall electrical properties of the slurry, thereby affecting the final photoelectric conversion efficiency.

[0035] That is to say, the preparation method of the sintered-cured conductive paste for TOPCon and BC of the embodiment of the present invention, by adding a suitable amount of thixotropic agent and demolding aid, allows the silver-coated copper powder to replace part of the silver powder, thereby preparing the sintered-cured conductive paste for TOPCon and BC, which greatly saves the process cost, and the process flow is also relatively simple and effective.

[0036] In some embodiments, in step S1, the silver powder includes a particle size D 50 Silver powder with a particle size of 1.5 μm and a particle size of D 50 50nm silver powder;

[0037] The particle size D of the silver-coated copper powder 50 3~5μm.

[0038] Specifically, the larger silver powder with a particle size of 1.5μm D50 and the smaller silver powder with a particle size of 50nm D50 are selected to construct a multi-level conductive network. The 1.5μm silver powder can serve as the skeleton of the conductive network, while the 50nm small silver powder can fill the skeleton gaps formed by the large silver powder, increasing the density and contact points of the conductive network, making the electronic conduction more delicate and uniform. The synergistic effect of the two can significantly improve the conductive performance. 50The addition of 3-5μm silver-coated copper powder is mainly due to comprehensive considerations of cost and performance. It not only takes advantage of the low cost of copper, but also ensures good conductivity and oxidation resistance with the help of the silver layer. In the conductive paste system, silver-coated copper powder can build a conductive network with two types of silver powder to further enrich and optimize the network structure, meeting the requirements of conductive performance while reducing costs.

[0039] In some embodiments, step S1 further includes adding a dispersant.

[0040] The particle size is D 50 Silver powder with a particle size of 1.5 μm and a particle size of D 50 The mass ratio of 50nm silver powder, silver-coated copper powder, glass powder, resin, solvent and dispersant is (5-30): (5-30): (60-80): (1-4): (0.5-3): (2-8): (0.1-0.5).

[0041] Specifically, silver powder with a D50 of 1.5 μm is selected. This larger silver powder is mainly responsible for constructing a macroscopic conductive path in the conductive paste. In the range of 5-30 parts by mass, it can provide a relatively long and fast conduction path for electrons. Reasonable allocation within the range of 5-30 parts by mass can achieve a good balance between conductive performance, stability and construction performance.

[0042] Silver powder with a D50 of 50nm can deeply fill the tiny gaps between the macroscopic conductive paths constructed by 1.5μm silver powder due to its tiny particle size. In the range of 5-30 parts by mass, it greatly improves the density of the conductive network and increases the number of contact sites for electronic conduction. And silver powder of this particle size can achieve a good dispersion state in the slurry with the synergistic effect of resin, solvent and dispersant, effectively preventing the occurrence of agglomeration.

[0043] Silver-coated copper powder with a D50 of 3-5μm (60-80 parts by mass) can significantly reduce production costs while ensuring certain conductivity. In addition, the silver layer on the outer layer of the silver-coated copper powder gives it good conductivity and antioxidant properties, while the internal copper core provides low-cost support. Within this mass ratio range, the silver-coated copper powder can give full play to its conductive properties, and through the synergistic effect with other silver powders and additives, it maintains good stability in the slurry system.

[0044] The core function of glass powder (1-4 parts by mass) is to promote the bonding between the components during high-temperature sintering. At 1-4 parts by mass, the glass powder melts at the sintering temperature and can fill the gaps between the silver powder and between the silver powder and the battery substrate, so that the silver powder forms a continuous and dense conductive layer, and significantly enhances the adhesion between the conductive layer and the substrate such as the battery silicon wafer. The content of glass powder plays a key role in regulating the sintering temperature range of the conductive slurry. Within the range of 1-4 parts by mass, the sintering temperature can be controlled in a suitable range. The appropriate glass powder content can not only ensure that it is fully melted during the sintering process to achieve a good bonding effect, but also avoid damage to other sensitive components of the battery due to excessive temperature.

[0045] When the resin is selected in an amount of 0.5 to 3 parts by mass, it can tightly bond solid components such as silver powder and glass powder together to form a continuous and uniform film layer. Within this mass range, the resin can give the slurry a suitable thixotropy, that is, when not subjected to shear force, the slurry maintains a high viscosity, effectively preventing the sedimentation of solid components such as silver powder; and during the construction process, such as screen printing or coating operations, under the action of shear force, the viscosity of the slurry rapidly decreases, becoming easy to flow, and facilitating the realization of a uniform coating or printing effect.

[0046] When the solvent is in the range of 2 to 8 parts by mass, sufficient fluidity can be provided to ensure that the slurry has an appropriate viscosity to meet the requirements of the construction operation.

[0047] The key mission of the dispersant in the conductive paste is to prevent the silver powder from agglomerating and ensure its uniform dispersion. In the range of 0.1 to 0.5 parts by mass, the dispersant can be adsorbed on the surface of the silver powder particles to form a stable protective film, effectively reducing the surface attraction between the silver powder particles.

[0048] Preferably, in step S1, the resin includes one or more of polyvinyl butyral, ABS resin, mixed epoxy resin, solid bisphenol A epoxy resin, pure monomer resin, phenolic resin, polymethyl methacrylate resin, polyvinyl acetate resin, thermoplastic acrylic resin or alkyd resin;

[0049] Preferably, in step S1, the solvent includes one or more of acetone, butanone, methyl isobutyl ketone, isophorone, ethylene glycol, propylene glycol, ethyl acetate, butyl acetate, xylene, terpineol, ethylene glycol ethyl ether, diethylene glycol butyl ether, dodecanol ester, dibutyl phthalate, dioctyl phthalate, dioctyl adipate, isopropanol, n-butanol, and cyclopentanone;

[0050] The dispersant includes one or more of polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene glycol, hexadecyl trimethyl ammonium chloride, octadecylamine acetate, oleic acid, stearic acid or palmitic acid. Specifically, wetting dispersants such as BYK111, BYK2009, BYK-220SN, BYK-1162 and the like can also be used.

[0051] In some implementations, step S2 specifically includes:

[0052] Add thixotropic agent and demoulding aid to the preliminary slurry, mix evenly to obtain a mixed slurry, grind the mixed slurry to obtain a sintering and curing conductive slurry for TOPCon and BC,

[0053] The mass of the thixotropic agent and the demoulding aid accounts for 0.05% to 1% and 0.1% to 5% of the mass of the sintering and curing conductive paste for TOPCon and BC respectively.

[0054] That is to say, after adding the thixotropic agent and the demoulding aid to the preliminary slurry and mixing them evenly, the slurry needs to be ground so that the quality of the obtained conductive slurry is better, that is, the rheological properties are better.

[0055] Preferably, in step S2, the thixotropic agent includes one or more of hydrogenated castor oil, polyvinyl alcohol, and hydroxyethyl cellulose.

[0056] Specifically, the above substances are selected as thixotropic agents, which can make the slurry spread better on the battery substrate and fill the tiny pores on the substrate surface, thereby improving the flatness of the conductive film. At the same time, the thixotropic agent helps the conductive components such as silver powder to be closely arranged in the film layer, reduce the gaps in the film layer, and increase the density of the film layer.

[0057] Preferably, in step S2, the demolding aid includes one or more of acrylic resin, polyurethane resin, polyester resin, and silicone resin.

[0058] Specifically, the above substances are selected as demoulding aids to ensure that the conductive paste can be completely released from the mold after printing, reduce the generation of surface defects of the printed graphics, and thus improve the appearance quality and uniformity of the conductive film.

[0059] In some embodiments, in step S2, grinding the mixed slurry specifically includes:

[0060] The mixed slurry is ground to a fineness of 0 to 10 μm.

[0061] Thus, the mixed slurry is ground to a predetermined fineness range of 0 to obtain a sintered and cured conductive slurry for TOPCon and BC, which reduces the size of its material particles and further improves the leveling property of the slurry.

[0062] The sintering-curing conductive paste for TOPCon and BC according to the embodiment of the second aspect of the present invention is prepared by the preparation method of the sintering-curing conductive paste for TOPCon and BC described in any embodiment of the first aspect.

[0063] The sintering and curing conductive paste for TOPCon and BC of the present application and the preparation method thereof are further described below with specific examples.

[0064] Example 1

[0065] Prepare a preliminary slurry: select 10 parts by mass of silver powder with a D50 of 1.5 μm, 70 parts by mass of silver-coated copper powder with a D50 of 4 μm, 10 parts by mass of silver powder with a D50 of 50 nm, 2.5 parts by mass of glass powder, 1.3 parts by mass of polyvinyl butyral, 5.9 parts by mass of acetone, and 0.3 parts by mass of polyethylene glycol, and mix them evenly to obtain a preliminary slurry.

[0066] Preparation of sintering-curing conductive paste for TOPCon and BC: Add 0.3 parts by mass of hydrogenated castor oil and 2 parts by mass of acrylic resin to the preliminary paste, mix them evenly, and grind them to a fineness of 1 μm to obtain sintering-curing conductive paste for TOPCon and BC.

[0067] Example 2

[0068] Prepare a preliminary slurry: select 10 parts by mass of silver powder with a D50 of 1.5 μm, 70 parts by mass of silver-coated copper powder with a D50 of 4 μm, 10 parts by mass of silver powder with a D50 of 50 nm, 2.5 parts by mass of glass powder, 1.3 parts by mass of polyvinyl butyral, 5.9 parts by mass of acetone, and 0.3 parts by mass of polyethylene glycol, and mix them evenly to obtain a preliminary slurry.

[0069] Preparation of sintering-curing conductive paste for TOPCon and BC: Add 0.3 parts by mass of polyvinyl alcohol and 4 parts by mass of silicone resin to the preliminary paste, mix them evenly, and grind them to a fineness of 1 μm to obtain sintering-curing conductive paste for TOPCon and BC.

[0070] Example 3

[0071] Prepare a preliminary slurry: select 10 parts by mass of silver powder with a D50 of 1.5 μm, 70 parts by mass of silver-coated copper powder with a D50 of 4 μm, 10 parts by mass of silver powder with a D50 of 50 nm, 2.5 parts by mass of glass powder, 1.3 parts by mass of polyvinyl butyral, 5.9 parts by mass of acetone, and 0.3 parts by mass of polyethylene glycol, and mix them evenly to obtain a preliminary slurry.

[0072] Preparation of sintering-curing conductive paste for TOPCon and BC: Add 0.1 parts by mass of hydroxyethyl cellulose and 2 parts by mass of polyester resin to the preliminary slurry, mix them evenly, and grind them to a fineness of 1 μm to obtain sintering-curing conductive paste for TOPCon and BC.

[0073] Comparative Example 1

[0074] Preparation of conductive paste: Select 10 parts by mass of silver powder with a D50 of 1.5 μm, 70 parts by mass of silver-coated copper powder with a D50 of 4 μm, 10 parts by mass of silver powder with a D50 of 50 nm, 2.5 parts by mass of glass powder, 1.3 parts by mass of polyvinyl butyral, 5.9 parts by mass of acetone, and 0.3 parts by mass of polyethylene glycol, and mix them evenly to obtain a conductive paste.

[0075] Comparative Example 2

[0076] Prepare a preliminary slurry: select 10 parts by mass of silver powder with a D50 of 1.5 μm, 70 parts by mass of silver-coated copper powder with a D50 of 4 μm, 10 parts by mass of silver powder with a D50 of 50 nm, 2.5 parts by mass of glass powder, 1.3 parts by mass of polyvinyl butyral, 5.9 parts by mass of acetone, and 0.3 parts by mass of polyethylene glycol, and mix them evenly to obtain a preliminary slurry.

[0077] Preparation of sintering-curing conductive paste for TOPCon and BC: Add 2 parts by mass of acrylic resin to the preliminary paste, mix evenly, grind to a fineness of 1 μm, and prepare sintering-curing conductive paste for TOPCon and BC.

[0078] Comparative Example 3

[0079] Prepare a preliminary slurry: select 10 parts by mass of silver powder with a D50 of 1.5 μm, 70 parts by mass of silver-coated copper powder with a D50 of 4 μm, 10 parts by mass of silver powder with a D50 of 50 nm, 2.5 parts by mass of glass powder, 1.3 parts by mass of polyvinyl butyral, 5.9 parts by mass of acetone, and 0.3 parts by mass of polyethylene glycol, and mix them evenly to obtain a preliminary slurry.

[0080] Preparation of sintering-curing conductive paste for TOPCon and BC: Add 0.3 parts by mass of hydrogenated castor oil to the preliminary paste, mix evenly, grind to a fineness of 1 μm, and prepare sintering-curing conductive paste for TOPCon and BC.

[0081] Table 1 is a performance test evaluation table of the sintered and cured conductive pastes for TOPCon and BC of each embodiment and the conductive pastes of each comparative example.

[0082]

[0083] The conductive pastes prepared in the embodiments and comparative examples were precisely sintered by laser with a wavelength of 800nm-2000nm to obtain the test data shown in Table 1.

[0084] Referring to Table 1, it can be seen from Example 1 and Comparative Example 1 that Example 1 is beneficial to improving the photoelectric conversion efficiency Eta by adding an appropriate amount of thixotropic agent hydrogenated castor oil and demolding aid acrylic resin.

[0085] It can be seen from Example 2 and Comparative Example 1 that the short-circuit current Isc can be significantly increased by adding an appropriate amount of thixotropic agent polyvinyl alcohol and demolding aid silicone resin, and excessive addition will lead to a significant increase in resistivity.

[0086] It can be seen from Example 3 and Comparative Example 1 that the short-circuit current Isc can be improved by adding the thixotropic agent hydroxyethyl cellulose and the demolding aid polyester resin, but the resistivity will be affected.

[0087] In Comparative Example 2, only acrylic resin as a demolding aid was added without the participation of a thixotropic agent, resulting in no significant improvement in the photoelectric conversion efficiency Eta.

[0088] In Comparative Example 3, only hydrogenated castor oil, a thixotropic agent, was added without any release agent, resulting in a loss of the filling factor FF and the photoelectric conversion efficiency Eta.

[0089] It can be seen that the sintering and curing conductive paste for TOPCon and BC prepared by the preparation method of the present invention can improve the photoelectric performance while reducing the production cost by adding a thixotropic agent and a demolding aid and replacing the silver powder with part of the silver-coated copper powder.

[0090] In addition, when the sintered and cured conductive paste for TOPCon and BC prepared by the preparation method of the present invention is overprinted on the silver seed layer, no protective gas is required in the process, and in the sintering process, a relatively small molecular weight organic resin that can volatilize in an environment within 450°C is used to meet the resistivity requirements of the high temperature paste, achieving a resistivity of less than 3.5μ Ω · cm.

[0091] The preparation method of the present invention can significantly reduce the cost when preparing the sintering and curing conductive paste for TOPCon and BC compared with the prior art, and there is no protective gas in the process; when the sintering and curing conductive paste for TOPCon and BC of the present invention is laser sintered with a wavelength in the range of 800nm-2000nm, it can effectively reduce the thermal impact on other structural layers of the battery and reduce energy consumption. By controlling the laser sintering process parameters, the conductive paste can form a uniform and dense conductive structure, significantly improving the conductive performance and photoelectric conversion efficiency of the battery. Compared with other copper processes, the steps are simple and effective.

[0092] At this point, those skilled in the art should recognize that, although multiple exemplary embodiments of the present invention have been shown and described in detail herein, many other variations or modifications that conform to the principles of the present invention can still be directly determined or derived based on the content disclosed in the present invention without departing from the spirit and scope of the present invention. Therefore, the scope of the present invention should be understood and recognized as covering all these other variations or modifications.

Claims

1. A method for preparing a sintered and cured conductive paste for TOPCon and BC, characterized in that: The steps include: S1, uniformly mixing silver powder, silver-coated copper powder, glass powder, resin and solvent to obtain a preliminary slurry; S2, adding a thixotropic agent and a demolding aid to the preliminary slurry, and mixing them evenly to obtain the sintering and curing conductive slurry for TOPCon and BC, The mass of the thixotropic agent and the demoulding aid accounts for 0.05% to 1% and 0.1% to 5% of the mass of the sintering and curing conductive paste for TOPCon and BC, respectively.

2. The method for preparing the sintered and cured conductive paste for TOPCon and BC according to claim 1, characterized in that: In the step S1, The silver powder includes a particle size D 50 Silver powder with a particle size of 1.5 μm and a particle size of D 50 50nm silver powder; The particle size D of the silver-coated copper powder 50 3~5μm.

3. The method for preparing the sintered and cured conductive paste for TOPCon and BC according to claim 2, characterized in that: The step S1 further includes adding a dispersant. Wherein, the particle size is D 50 The silver powder is 1.5 μm, and the particle size is D 50 The mass ratio of the 50nm silver powder, the silver-coated copper powder, the glass powder, the resin, the solvent and the dispersant is (5-30): (5-30): (60-80): (1-4): (0.5-3): (2-8): (0.1-0.5).

4. The method for preparing the sintered and cured conductive paste for TOPCon and BC according to claim 3, characterized in that: In the step S1, The resin includes one or more of polyvinyl butyral, ABS resin, mixed epoxy resin, solid bisphenol A epoxy resin, pure monomer resin, phenolic resin, polymethyl methacrylate resin, polyvinyl acetate resin, thermoplastic acrylic resin or alkyd resin.

5. The method for preparing the sintered and cured conductive paste for TOPCon and BC according to claim 3, characterized in that: In the step S1, The solvent includes one or more of acetone, butanone, methyl isobutyl ketone, isophorone, ethylene glycol, propylene glycol, ethyl acetate, butyl acetate, xylene, terpineol, ethylene glycol ethyl ether, diethylene glycol butyl ether, dodecanol ester, dibutyl phthalate, dioctyl phthalate, dioctyl adipate, isopropanol, n-butanol, and cyclopentanone; The dispersant includes one or more of polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene glycol, hexadecyltrimethylammonium chloride, octadecylamine acetate, oleic acid, stearic acid or palmitic acid.

6. The method for preparing the sintered and cured conductive paste for TOPCon and BC according to claim 1, characterized in that: The step S2 specifically includes: Adding a thixotropic agent and a demoulding aid to the preliminary slurry, uniformly mixing to obtain a mixed slurry, grinding the mixed slurry to obtain the sintering and curing conductive slurry for TOPCon and BC, The mass of the thixotropic agent and the demoulding aid accounts for 0.05% to 1% and 0.1% to 5% of the mass of the sintering and curing conductive paste for TOPCon and BC, respectively.

7. The method for preparing the sintered and cured conductive paste for TOPCon and BC according to claim 1, characterized in that: In the step S2, The thixotropic agent includes one or more of hydrogenated castor oil, polyvinyl alcohol, and hydroxyethyl cellulose.

8. The method for preparing the sintered and cured conductive paste for TOPCon and BC according to claim 1, characterized in that: In the step S2, The demoulding aid includes one or more of acrylic resin, polyurethane resin, polyester resin and silicone resin.

9. The method for preparing the sintered and cured conductive paste for TOPCon and BC according to claim 6, characterized in that: In the step S2, grinding the mixed slurry specifically includes: The mixed slurry is ground to a fineness of 0 to 10 μm.

10. A sintering and curing conductive paste for TOPCon and BC, characterized in that: The TOPCon and BC are prepared by the method for preparing sintering and curing conductive paste according to any one of claims 1 to 9.